The preventive health care act and the future forum public health in Germany. (13th November 2019) - De Bock, F; Shajanian Zarneh, Y; Matusall, S
Abstract: The public health system in Germany, similar to education and cultural affairs, is characterised by the federal structure. It is mainly regulated and decided at the state and municipal level, and not primarily at the national level. The preventive health care act (The Act to Strengthen Health Promotion and Preventive Health Care) (2015) underlines the setting-based approach of health promotion and takes a life course perspective by recommending goals of growing up healthy, living and working healthy and healthy ageing. The act formulates broad recommendations for prevention and health promotion at the national level, that in turn take on concrete forms in mandatory framework agreements at the federal state level with uniform health objectives. On the whole, the key objective of the act is to improve preventive health care and general health promotion. Also the financing of the act by the mandatory health insurance is a special feature and at the same time a novelty. At the same time a bottom-up project has been recently launched with the aim to develop a public health strategy in Germany. The project future forum public health (ZfPH) is a platform for public health professionals, researchers and students following incorporated concepts of policy analysis as well as methods that will ensure participation, transparency and transferability of the results into policy and practice. Over the next three years, ZfPH's steering group will moderate a participatory process, including stakeholders from public health practice and research as well as policy makers. In an evidence-based approach, they will first analyse the current state of Germany's public health system before developing concrete policy recommendations for a coherent and efficient public health system. The presentation will give a short overview over the German public health system and the preventive health care act, its structure and the achievements as well as the bottom-up project future forum public health.